2009
DOI: 10.4028/www.scientific.net/kem.407-408.85
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Method of Improving Accuracy of Parallel Machine Tools

Abstract: The paper puts forward a method that the internal force greatly improves the actual accuracy of parallel machine tools, and a-2DOF redundantly actuated parallel mechanism is designed. The position and speed harmonious control conditions is studied and the force control system is devised in this paper. The experiments show that this method can greatly improve the accuracy of parallel machines. Therefore, the results provide the theoretical and experimental foundation for improving the accuracy of parallel machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The first method is that the driving forces/torques are distributed without internal forces [18,35,70]. A number of studies have shown that the internal forces can be utilized to change the stiffness [79], improve the motion accuracy [32], increase the load-carrying capacity [19], and eliminate the backlash [34] of active overconstrained PMs, so the second method is that the driving forces/torques are distributed by utilizing the advantages of internal forces [19,32,34].…”
Section: Methods Based On the Optimal Internal Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first method is that the driving forces/torques are distributed without internal forces [18,35,70]. A number of studies have shown that the internal forces can be utilized to change the stiffness [79], improve the motion accuracy [32], increase the load-carrying capacity [19], and eliminate the backlash [34] of active overconstrained PMs, so the second method is that the driving forces/torques are distributed by utilizing the advantages of internal forces [19,32,34].…”
Section: Methods Based On the Optimal Internal Forcesmentioning
confidence: 99%
“…It is well known that redundantly actuated PMs [19][20][21] have been investigated and utilized extensively, since redundant actuations can avoid kinematic singularities [22][23][24][25][26][27], enlarge load capability [28][29][30], improve dynamic characteristics [31,32], and eliminate backlash [33,34] of the mechanisms. The distribution of driving forces/torques of a redundantly actuated PM belongs to the statically indeterminate problem.…”
Section: Introductionmentioning
confidence: 99%